Multidimensional assessment of the energy sustainability and carbon pricing impacts along the Belt and Road Initiative. (February 2022) - Bompard, E.F.; Corgnati, S.P.; Grosso, D.; Huang, T.; Mietti, G.; Profumo, F.
Abstract: After its establishment in 2013, the Belt and Road Initiative (BRI) has rapidly developed, and it has brought together countries from all over the world. The BRI countries of Eurasia cover nearly 40% of the land surface and, in particular, the energy dimension of BRI is a dynamic and impacting reality: countries connected by the BRI account for 54% of world primary energy supply. In this global framework, it is of uttermost importance to evaluate the behaviour of BRI countries towards energy sustainability issues, by providing an overview of the current situation and assessing its evolution over time. In our analysis, we develop a quantitative framework for sustainability analysis, based on four dimensions: society, economy, energy and environment. The different dimensions are integrated in an overall sustainability index, evaluated through Multi Criteria Decision Analysis and in particular PROMETHEE II. We consider the most impacting (in terms of energy) BRI countries and we implement a comparative analysis of their sustainability providing a ranking and tracking their time evolution. Furthermore, we analyse the current practises of carbon pricing (carbon tax or Emission Trading System) along BRI, when implemented, as these mechanisms can contribute in reducing emissions and improving sustainability, also resulting in a benefit for the economy and society. For this aim, we use the proposed quantitative framework for assessing their effects on BRI sustainability. Highlights: BRI countries cover more than 50% of World GDP, energy consumption and CO2 emissions. The sustainability of countries is assessed with a multi-dimensional approach (MCDA). Carbon pricing can enhance economic, social, energy and environmental sustainability. Europe has the highest sustainability level for its environmental and social policies. Kazakhstan, China and Europe improve in sustainability also thanks to carbon pricing.